Preparation of b-enamino carbonylic compounds using microwave radiation/K-10 - Braibante Hugo T. S.; Braibante Mara E. F.; Rosso Giovanni B.; Oriques Daniela A. (Journal of the Brazilian Chemical Society, 2003)
The preparation of beta-enamino ketones and esters using the methodology of the reactions on solid support coupled with microwave irradiation is described. The reaction of cyclic, acyclic and alpha-chloro-substituted beta-dicarbonyl compounds with amines or their corresponding ammonium acetates was carried out using K-10 as solid support and a domestic microwave oven as the radiation source to give beta-enamino carbonylic compounds in good yields.